How and when does syntax perpetuate stereotypes? Probing the framing effects of subject-complement statements of equality. (3rd April 2022) - Holmes, Kevin J.; Doherty, Evan M.; Flusberg, Stephen J.
Abstract: Although subject-complement statements like "girls are as good as boys at math" appear to express gender equality, people infer a gender difference : the group in the complement position (boys) is judged superior. We investigated (1) whether this syntactic framing effect generalizes to other socially charged inferences and (2) whether awareness of the bias implied by the syntax mitigates its influence. Across four preregistered experiments ( N = 2, 734), we found reliable framing effects on inferences about both math ability and terrorist behavior, but only for the small subset of participants (∼30%) who failed to identify the influence of the subject-complement statements on their judgments. Most participants did recognize this influence, and these participants showed reduced or even reversed framing effects; they were also more likely to explicitly judge subject-complement syntax as biased. Our findings suggest that this syntax perpetuates stereotypes only when people are oblivious to, or unmotivated to interrogate, its implications.